Coagulation Factors in Pregnant Women and Premature Infants with and without the Respiratory Distress Syndrome - Markarian, Marguerite; Lindley, Annabelle; Jackson, Jacqueline J.; Bannon, Anne (Thrombosis and Haemostasis, 1967)
Coagulation factors (accelerator globulin, antihemophilic globulin, specific prothrombin, proconvertin complex and Stuart-Prower factor) in 82 low birth weight infants (750–1750 g), 22 normal adult controls and 38 pregnant women prior to delivery were studied at San Borja Hospital in Santiago, Chile.Pregnant women prior to delivery had significantly higher values of accelerator globulin, antihemophilic globulin, proconvertin complex and Stuart-Prower factor than adult controls, but there was no difference in specific prothrombin.The coagulation factors were similar in premature infants without RDS as compared to those with RDS (lived and died combined). However, premature infants with RDS who lived had higher values of prothrombin, proconvertin complex, Stuart-Prower factor at 25 hrs and accelerator globulin at 55 hrs of age than those with RDS who died. Most of these findings could be explained by impaired liver function in association with hypoxia.